2021
DOI: 10.1186/s13046-021-02027-0
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_001422 promotes the progression and metastasis of osteosarcoma via the miR-195-5p/FGF2/PI3K/Akt axis

Abstract: Background Circular RNAs (circRNAs) are involved in diverse processes that drive cancer development. However, the expression landscape and mechanistic function of circRNAs in osteosarcoma (OS) remain to be studied. Methods Bioinformatic analysis and high-throughput RNA sequencing tools were employed to identify differentially expressed circRNAs between OS and adjacent noncancerous tissues. The expression level of circ_001422 in clinical specimens a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 51 publications
(52 reference statements)
2
51
0
Order By: Relevance
“…The lower chamber was fulfilled with 600 μ L DMEM containing 10% FBS as an attractant. After 24 h of culture, cells were fixed on the lower surface with paraformaldehyde (4%), stained with crystal violet (0.1%), and viewed using inverted light microscopy [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower chamber was fulfilled with 600 μ L DMEM containing 10% FBS as an attractant. After 24 h of culture, cells were fixed on the lower surface with paraformaldehyde (4%), stained with crystal violet (0.1%), and viewed using inverted light microscopy [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Control probes and biotinylated circ-RANGAP1 and miR-542-3p probes (RiboBio, Guangzhou, China) were incubated with C-1 magnetic beads (LifeTechnologies, USA) for 2 h. Cell lysates were incubated with biotinylated circ-RANGAP1 and miR-542-3p probes, and RNA was extracted using RNeasy Mini Kit (Qiagen, USA), followed by measurement of circ-RANGAP1 and miR-542-3p expressions in the RNA complex [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next, eight hub genes were identified by Cytoscape: CXCR4, PDGFRB, CXCL10, B2M, CD86, CSF1R, TYROBP, and FGF2. CXCR4 ( Zhu et al, 2018 ), CSF1R ( Smeester et al, 2020 ), and FGF2 ( Yang et al, 2021 ) have been shown to promote OS progression. PDGFRB ( Liu et al, 2018 ), CXCL10 ( Niu et al, 2020 ), CD86 ( Jin et al, 2019 ), and TYROBP ( Wang et al, 2021 ) were identified as hub genes according to bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the role of lncRNAs and their target genes in cervical LN metastasis of OSCC, we identified the differentially expressed mRNAs and lncRNAs between primary OSCC samples with and without regional LN metastasis, since the expression pattern of primary tissues was similar to that of metastatic tissues according to the single cell sequencing result of head and neck squamous cell carcinoma in 2017 [ 15 ]. The DERNAs were enriched in GO components and KEGG pathways associated with tumor progression, migration and invasion, such as cell adhesion [ 16 , 17 ], channel and receptor activity [ 18 20 ], cAMP signaling pathway [ 21 ], PI3K-AKT signaling pathway [ 22 , 23 ], cytokine-cytokine receptor interaction, and CAMs [ 24 ]. The DElncRNA-DEmRNA network was subsequently constructed, and LEMD1-AS1 and its antisense mRNA LEMD1 were identified as a relevant pair in OSCC.…”
Section: Discussionmentioning
confidence: 99%